Testing the Low-density Hypothesis for Reversed Sex Change in Polygynous Fish: Experiments in Labroides dimidiatus - Kuwamura, Tetsuo (Nature Publishing Group, 2014)
Hermaphroditism is ubiquitous among plants and widespread in the animal kingdom. It is an unsolved problem why reversed sex change has evolved in polygynous and protogynous reef fish. We have previously suggested that facultative monogamy occurs in low-density populations of polygynous species and that males that become single as a result of accidental mate loss may change sex when they meet larger males. In this study, to test this ‘low-density hypothesis', we conducted field experiments with the coral reef fish Labroides dimidiatus in which a portion of females were removed to create a low-density situation. The ‘widowed' males moved to search for a new mate when no male, female or juvenile fish migrated into their territories and paired with nearby single fish, whether male or female. Alternatively, males expanded their territories to take over the nearest pair whose male was much smaller. These results support our low-density hypothesis.